Синекологічні засади діагностики трансформації структурно-функціональної організації лісових екосистем в аспекті еволюції - Лавров, В.В.; Блінкова, О.І.; Мірошник, Н.В.; Іваненко, О.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. Methodological approaches in forestry studies differ in analysis of structural and functional components of ecosystems. This leads to receiving incomplete information, under the terms of influenced ecological factors. Methods. Theoretical methods of system-structural, retrospective and comparative analysis were combined with special methods of forestry, synecology, mycology. Results and conclusions. The system of syneсological methods is the basis of identify of the classification type of forest ecosystem; clarification of place in landscape and time trend of succession; determine the conditions and prospects of its development; explain the mechanisms and consequences of change stability and performance. Diagnostic indicators of violation of forest ecosystems are analysis of sensitive species, ecosystem engineer species, forest-forming species, determinants of consortiums, forms of symbiosis, co-adaptation interrelations, alien species. Keywords: synecology, forest ecosystem, structural and functional components, indicators.